Metode Mobile-D untuk Pengembangan Aplikasi Sales Performance Management Berbasis Real-Time Geotagging dan Area Mapping - Wisnu Wendanto; Tutus Praningki (JURIKOM (Jurnal Riset Komputer), 2026)
Sales often work outside the office to visit clients, hold meetings, and conduct surveys, making their activities difficult to monitor directly. This situation can lead to decreased productivity, missed targets, and reduced company profits. Sales activity management plays an important role in improving the effectiveness of a company’s marketing strategy. However, monitoring sales activities often faces several challenges due to manual recording processes and the lack of accurate location-based information. This study aims to develop a mobile-based Sales Performance Management system that utilizes geotagging and area mapping technologies to support more effective monitoring of sales activities. The system development adopts the Mobile-D method, which emphasizes an iterative and adaptive approach to mobile application development. The proposed system enables sales personnel to record customer visit activities through a mobile device equipped with a geotagging feature integrated with Google Maps services. The collected location data are then visualized through area mapping to provide a clearer overview of sales activity distribution. This functionality allows managers to monitor field activities and evaluate sales performance more efficiently. The implementation results indicate that the system is documenting sales activities accurately while supporting the validation process conducted by managers. In addition, the mapping feature provides useful insights into the spatial distribution of sales activities across different operational areas. Therefore, the developed system can improve the effectiveness of monitoring processes and managing sales personnel performance more efficiently.